2011
DOI: 10.1080/02602938.2010.488794
|View full text |Cite
|
Sign up to set email alerts
|

Changes in instructors' assessment thinking related to experimentation with new strategies

Abstract: Formative assessment has been recognised as a critical element in teaching for conceptual development. A case study research design was employed to: (1) characterise the assessment thinking of three science instructors at a researchbased university; and (2) examine the complex relationship between instructor thinking and practice by encouraging experimentation with alternative assessment strategies. Interviews, reflective journals, field notes and course documents were the data sources used to create a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…Some studies have confirmed that thinking drives approaches to teaching (Trigwell and Prosser 1996) and to assessment (Samuelowicz and Bain 2002), whilst others argue that practice helps shape conceptions, also with respect to teaching (Eley 2006) as well as assessment (Offerdahl and Tomanek 2011). The particular approach taken in the current research helps to illuminate the 'constructedness' of understandings of assessment, their intricate connection to practice and the multi-directionality of the relationship.…”
Section: Construction Of Understandingmentioning
confidence: 88%
See 2 more Smart Citations
“…Some studies have confirmed that thinking drives approaches to teaching (Trigwell and Prosser 1996) and to assessment (Samuelowicz and Bain 2002), whilst others argue that practice helps shape conceptions, also with respect to teaching (Eley 2006) as well as assessment (Offerdahl and Tomanek 2011). The particular approach taken in the current research helps to illuminate the 'constructedness' of understandings of assessment, their intricate connection to practice and the multi-directionality of the relationship.…”
Section: Construction Of Understandingmentioning
confidence: 88%
“…However, little is known about the exact nature of what was termed 'alternative practices' and details of the ways in which practices were affected by variations in conceptions. Offerdahl and Tomanek's (2011) longitudinal study paints a more complex picture of the relationship between thinking and practice in relation to assessment. They report that thinking about assessment became more sophisticated through practical experimentation with formative assessment strategies, but such revised thinking did not necessarily lead to changes in subsequent practice.…”
Section: Link Between Understanding and Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Calls for research exploring the holistic interaction (and effects) among learners and the learning environment afforded by TEFA remain unanswered (Kay & LeSage, 2009). Second, the validity and reliability of many studies have been limited in their measurement of only students' perceptions of engagement and learning by the use of only one or two quantitative items (Offerdahl & Tomanek, 2011) and because they rely on anecdotal data which draws strong criticism (Ha & Finkelstein, 2013). A more rigorous approach is necessary to capture educational benefits and challenges reflective of all involved in TEFA.…”
Section: Emergence Of Technology-enhanced Formative Assessmentsmentioning
confidence: 99%
“…His work described teachers' emphasis on the local immediate context rather than accessing "higher level conceptions of prac-tice. Similarly, recent case studies in assessment 'thinking' in higher education indicated that, although university teachers could learn more sophisticated thinking about assessment, this may not lead to changed assessment practices" (Offerdahl & Tomanek, 2011).…”
Section: Operational Level Decisionsmentioning
confidence: 99%